INFLUENCE OF OPHIOLITIC ROCKS ON THE SPATIAL DISTRIBUTION OF CHROMIUM AND NICKEL IN STREAM SEDIMENTS OF THE CECINA RIVER BASIN (TUSCANY, ITALY) - Laterza, Vittoria; Franceschini, Fabrizio (Ofioliti, 2013)
The concentrations of Cr and Ni and other heavy metals (Cd, Cu, Pb, Zn) have been determined in stream sediments collected into the Cecina River basin (Tuscany, Italy) in order to evaluate Cr and Ni levels and their spatial distribution and origin. An aqua regia digestion coupled to ICP-MS analysis has been performed on the samples. The distribution of Cr and Ni concentration as a function of grain size was also investigated, comparing finer samples (< 63 µm) and coarse samples (< 2000 µm). In Possera Creek samples, a left tributary of the Cecina River, another sieve fraction (< 125 µm) was sampled. The high lev- els of Cr and Ni in the stream sediments often exceed the thresholds of the Italian law currently in force (Legislative Decree No. 152/2006). Multivariate data analysis techniques (Hierarchical Clustering Analysis, HCA) were used to obtain information about the potential sources of heavy metals. The results indicate an Cr and Ni enrichment in stream sediments due to the presence of some extensive outcrops of serpentinized ultramafic rocks (ophiolites). The enrichment is major in the < 2000 µm fraction compared to the < 63 µm fraction.